Students e-learning access in select higher learning institutions of less-economically developed south east asian nations: Implications for economics of education - Alanya Beltran, Joel Elvys (2021)
Because of the growing pandemic of Corona Virus Disease-2019, Higher Education Institutions (HEIs) must utilize electronic learning (e-learning). Today's work economy, which is forever in flux because of the creation of new jobs and the continual disappearance of old ones, necessitates an on-the-job shift. Despite HEIs in less-wealthy nations like some countries of Asia being developed countries, in essence, it is much more difficult for students and teachers at these higher learning institutions to deal with the transition to e-learning due to their tight financial restrictions. This study sought to determine whether learners at the start of the COVID-19 Era were ready for e-learning and a connection between demographic variables and readiness for e-learning. A quantitative survey obtained information from 1200 students from elite higher educational institutions in South East Asia. A majority of respondents' scores lacked on the Online Learner Readiness Self-Assessment (OLRS). Inadequate OLRS findings among younger, female, and rural respondents. Factors affecting the success of students on the OLRS were age, sex, family socioeconomic status, and where they lived in the neighborhood. The inferences drawn from the study's findings would serve as an excellent benchmark to improve the delivery of elearning processes.